Public Service System at The Monano Sub-District Office in North Gorontalo as an Implementation of Good Governance in The Pandemic Era - Noviyanti Tue; Fatma Ngabito; Saharuddin Saharuddin; Achmad Risa Mediansyah; Sri Nur Ataqiyah Tomayahu (Ideas Publishing, 2023)
The government strives to provide more significant services during the pandemic. This study aims to understand the public service system at the North Monano Gorontalo District office as an embodiment of Good Governance. Utilizing a descriptive qualitative approach, the research gathers data. Findings indicate that public service quality at the Monano Sub-District office in Gorontalo Regency is good but not yet optimal, with some shortcomings requiring improvement. The research's implications are to enhance service quality and bring services closer to the community at the Monano Sub-District office.